Luther : based on a true story - Till, Eric (Quezon City : Magnavision.)
Martin Luther had one goal: Peace with God. He found it in Christ alone. Defying highest authorities in church and state Luther started the oldest continuing evangelical movement in the church history. This is his dramatic story. Armed with no more than his faith and quick wit, one man confronts the greatest powers on earth. Martin Luther's (Joseph Fiennes) bold actions foster an era of personal and religious freedoms unprecedented in history. A young law student, Luther abruptly enters a monastery when he believes his life is spared during a violent lightning storm. Luther proves to be an eager, apt disciple and is selected to travel to Rome on church business. He enters the Holy City with wide-eyed ideals of a young man-only to have them shattered.